Live imaging of stem cells: answering old questions and raising new ones. (December 2016) - Park, Sangbum; Greco, Valentina; Cockburn, Katie
Abstract : Stem cells are essential for both tissue maintenance and injury repair, but many aspects of stem cell biology remain incompletely understood. Recent advances in live imaging technology have allowed the direct visualization and tracking of a wide variety of tissue-resident stem cells in their native environments over time. Results from these studies have helped to resolve long-standing debates about stem cell regulation and function while also revealing previously unanticipated phenomena that raise new questions for future work. Here we review recent discoveries of both types, with a particular emphasis on how stem cells behave and interact with their niches during homeostasis, as well as how these behaviours change in response to wounding.